1999
DOI: 10.1074/jbc.274.49.34981
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of the Detergent-solubilized and Vesicle-reconstituted Insulin Receptor

Abstract: Insulin binding to the insulin receptor initiates a cascade of cellular events that are responsible for regulating cell metabolism, proliferation, and growth. We have investigated the structure of the purified, functionally active, human insulin receptor using negative stain and cryo-electron microscopy. Visualization of the detergent-solubilized and vesicle-reconstituted receptor shows the ␣ 2 ␤ 2 heterotetrameric insulin receptor to be a three-armed pinwheel-like complex that exhibits considerable variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…virtually all structural forms seen previously in electron microscopic examinations of the IR, except for long parallel T-shaped structures occasionally observed (45,46). This includes Y, H, V, and X shapes and parallel barlike images, observed by two-dimensional electron microscopy of detergent-solubilized IR, its ectodomain, or vesicle-reconstituted insulin-IR complex (45)(46)(47)(48).…”
Section: Minireview: Three-dimensional Structural Interactions 27331mentioning
confidence: 82%
See 2 more Smart Citations
“…virtually all structural forms seen previously in electron microscopic examinations of the IR, except for long parallel T-shaped structures occasionally observed (45,46). This includes Y, H, V, and X shapes and parallel barlike images, observed by two-dimensional electron microscopy of detergent-solubilized IR, its ectodomain, or vesicle-reconstituted insulin-IR complex (45)(46)(47)(48).…”
Section: Minireview: Three-dimensional Structural Interactions 27331mentioning
confidence: 82%
“…3d). Moreover, this structure, together with the insulinbound three-dimensional structure, makes it possible to reconcile (45)(46)(47)(48). Sixth column, modeled structures based on Fig.…”
Section: The Mechanics Of Transmembrane Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our structural studies of the covalent disulfide-linked ␣ 2 ␤ 2 heterodimeric insulin receptor do indeed reveal a Y-shaped receptor (Ref. 40; see also Ref. 41).…”
Section: Figmentioning
confidence: 99%
“…These studies have suggested either extended Tor Y-shaped receptor conformations (11,42,43) or more globular conformations (44 -46) but no clear consensus has emerged. The high affinity obtained with mIR.Fn0/Ex10 suggests that the first four domains, L1/Cys/L2/Fn0 and the Ex10 domain are in close proximity in the IR structure and that these most likely are the only domains interacting with the insulin molecule.…”
Section: Table I Insulin Affinity Of Recombinant Receptors In Variousmentioning
confidence: 99%